‘n Johannese Ekklesiologie? - Potgieter, S. T. (Verbum et ecclesia, 2002)
A Johanine Ecclesiology? In this research certain theological concepts in the so-called farewell discourses of Jesus in John 13:1-17:26 is systematised. These theological concepts are identified as the unique characteristics belonging to a group of people who is described as "Jesus’ own" in the passage referred to. They are characterised as a communion of faith, love, service, joy and peace, prayer, teaching, and unity as well as a community of the Holy Spirit, and missionary. It is shown that the portrayal of this group primarily corresponds to the characteristics of a first century Mediterranean family. A normal relationship between a father and son is activated when analogical references are made to God as Father and Jesus as Son. Normal people receive the status of children of God as well as the unique features that set them apart from the world, through a spirited birth process. An alternative lifestyle is expected of God's family in a hostile world, characterized by hate.